(untitled) - Arnold, John (Hoboken, N.J., 2007)
Complete with tables, illustrations, and figures, this valuable textbook includes problems and laboratories at the end of each chapter and also offers a number of exercises that allow students to implement the various techniques discussed using MATLAB. The authors' coverage of implementation and theory makes this a practical reference for professionals, as well as an indispensable textbook for advanced undergraduates and graduate-level students in electrical engineering and computer science programs.
Keywords: Digital television,Truyền hình số